3D printed micro-fluidic chip as well as preparation method and application thereof
The 3D printed microfluidic chip prepared by FDM technology uses quartz sand and ABS materials to solve the problem that traditional experimental methods are difficult to control experimental conditions on the microscopic scale, and achieves efficient and low-cost hydrate research simulation, with excellent chemical stability and low adsorption properties.
Patent Information
- Application Number
- CN202411757251.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-12-03
AI Technical Summary
Traditional experimental methods are difficult to accurately control experimental conditions on the microscopic scale, cannot thoroughly study the formation and decomposition process of hydrates, and are cost-effective and inefficient.
The 3D-printed microfluidic chip was prepared by melt deposition molding (FDM) technology, using quartz sand powder as the main frame raw material, and filling the channels of the chip through acrylonitrile-butadiene-styrene copolymer (ABS). Combined with the degreasing and sintering process, a microfluidic chip with high hardness, strength and chemical stability was obtained.
It realizes the precise simulation of the hydrate generation environment at the microscopic scale, improves the hardness, strength and dimensional stability of the chip, reduces the preparation cost and time, and enhances the chemical stability and low adsorption properties of the chip.
Smart Images

Figure CN119502330A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of hydrates, and in particular relates to a 3D printed microfluidic chip and a preparation method and application thereof. Background Art
[0002] Hydrate is a crystalline substance formed by water and gas molecules under certain temperature and pressure conditions. In the energy field, natural gas hydrate is considered to be a future energy resource with great potential. In addition, hydrates also have an important impact on the stability of seabed geological structures and global climate change. Therefore, the study of the formation, decomposition mechanism and related physical and chemical properties of hydrates has extremely important scientific significance and practical application value. In hydrate research, traditional experimental methods often have some limitations. For example, it is difficult to accurately control the experimental conditions with macro-scale experimental equipment, and it is impossible to deeply study the formation and decomposition process of hydrates at the microscopic scale. Moreover, traditional experimental methods usually require a large number of samples and a long experimental cycle, which is costly and inefficient. When studying the microstructure and kinetic properties of hydrates, traditional methods also face great challenges.
[0003] Microfluidic chip technology has the characteristics of miniaturization, integration, and high throughput. It can accurately control the flow and reaction conditions of fluids at a microscopic scale, providing a new means for hydrate research. Through microfluidic chips, the formation environment of hydrates in nature can be simulated, and the nucleation, growth and decomposition processes of hydrates, as well as the interaction between hydrates and the surrounding environment can be studied. In addition, microfluidic chips can also be combined with various detection technologies to achieve real-time monitoring and analysis of hydrate-related parameters. Among the existing 3D printing technologies, the post-processing of photocuring 3D printing is complex and costly; the selection of selective laser sintering materials is limited, the equipment is complex and the cost is high; digital light processing has light scattering problems; and inkjet 3D printing nozzles are prone to clogging.
[0004] As a rapid prototyping technology, fused deposition modeling (FDM) technology has unique advantages in the preparation of microfluidic chips. FDM technology can quickly and inexpensively manufacture microfluidic chips with complex structures to meet the needs of different experimental designs in hydrate research. At the same time, FDM technology can be printed using a variety of materials, providing more possibilities for the functionalization and customization of microfluidic chips. Compared with traditional microfluidic chip preparation methods, FDM technology is more flexible and efficient, and can greatly shorten the preparation cycle of microfluidic chips and reduce costs. Common materials for making microfluidic chips include silicon, glass, and high molecular polymers, but these materials cannot simulate the formation environment of hydrates in actual reservoirs very well. For this reason, a suitable material and supporting technology are needed to realize the preparation of microfluidic chips serving the hydrate field. Summary of the invention
[0005] In view of the deficiencies in the prior art, a first object of the present invention is to provide a method for preparing a 3D printed microfluidic chip.
[0006] The second object of the present invention is to provide a 3D printed microfluidic chip prepared by the above preparation method. The 3D printed microfluidic chip provided by the present invention has higher hardness and strength, better dimensional stability, and the size of the chip changes less when stress or temperature changes; it has excellent chemical stability and low adsorption, and is not easy to adsorb or react with chemical reagents. The most important thing is that quartz sand (stone-like material) has good surface wettability and can well simulate the hydrate reservoir environment.
[0007] The third object of the present invention is to provide an application of a 3D printed microfluidic chip prepared by the above preparation method.
[0008] In order to achieve the above object, the present invention adopts the following technical solution:
[0009] The invention discloses a preparation method of a 3D-printed microfluidic chip. The method comprises the following steps: mixing, granulating and drawing quartz sand micropowder and a binder to obtain a wire material A; then granulating and drawing acrylonitrile-butadiene-styrene copolymer (ABS) to obtain a wire material B; respectively placing the wire material A and the wire material B into two feed ports of an FDM 3D printer, and performing extrusion deposition printing through a nozzle according to a model of the microfluidic chip, wherein the wire material A prints a microfluidic chip body, and the wire material B fills a channel of the microfluidic chip to obtain a microfluidic chip green body, and the microfluidic chip green body is degreased and sintered to obtain the microfluidic chip.
[0010] The preparation method of the present invention adopts fused deposition modeling (FDM) technology to prepare a microfluidic chip, wherein quartz sand powder is used as the main frame raw material of the microfluidic chip, and the finally formed microfluidic chip can better simulate the generation environment of hydrates in actual reservoirs. In addition, in the present invention, during the printing process, a wire material B formed by acrylonitrile-butadiene-styrene copolymer as a raw material is simultaneously used to fill the channel of the microfluidic chip, and the finally filled wire material B is degreased to obtain a smooth channel of the microfluidic chip.
[0011] In the present invention, it is crucial to use ABS as the filling filament. As the filling filament, ABS can, on the one hand, provide a temporary support structure for the channel during the printing process, ensure that the channel maintains the designed shape during the molding process, and prevent the channel wall from collapsing or deforming; on the other hand, it can prevent the filament A from excessively entering the channel during the quartz sand integrated printing chip, thereby preventing the channel from being blocked during the printing process and ensuring the connectivity of the channel. More importantly, ABS has a certain interface interaction with quartz sand; it can be removed together in the fat dissolving stage, which greatly simplifies the process.
[0012] In the actual exploration process, the inventors also tried other materials as filament B, but the results were not good. For example, when trying to use polylactic acid as filament B to fill the microfluidic chip channel, it was found that the mechanical properties of PLA were relatively weak, and its channel support ability was not as good as ABS, which could easily lead to local collapse of the channel wall during the molding process, affecting the shape accuracy of the channel. In addition, the degreasing process of PLA is also different from that of ABS, and some substances may remain on the surface of the channel, affecting the smoothness of the channel and further affecting the flow characteristics of the fluid.
[0013] In a preferred embodiment, the binder is composed of the following by mass percentage: 50%-60% polyurethane resin, 10%-15% γ-aminopropyltriethoxysilane, 10%-15% dibutyl phthalate, 5%-10% nano titanium dioxide, 5%-10% polytetrafluoroethylene powder, and 1%-2% antioxidant 168.
[0014] In the present invention, quartz sand powder can be made into a material for FDM3D printing, which is crucial for the formulation of the binder, and the bonding, bonding and plasticizing capabilities provided by each component play a corresponding key role. Specifically, polyurethane resin plays a key bonding role in the manufacture of microfluidic chips, tightly combining loose quartz sand particles to form a stable structure, and its flexibility helps to buffer external stress during manufacture and use, and prevents the quartz sand structure from breaking due to temperature changes. γ-aminopropyl triethoxysilane forms a chemical bond on the surface of quartz sand, and γ-aminopropyl triethoxysilane significantly improves the bonding strength between quartz sand and polyurethane resin, and can also improve the surface properties of quartz sand and adjust the surface hydrophilicity or hydrophobicity of quartz sand. Dibutyl phthalate, as a plasticizer, can adjust the flexibility of quartz sand and the binder system, and by interacting with polyurethane resin, dibutyl phthalate can adjust the hardness of quartz sand materials. The addition of nano-titanium dioxide can significantly improve the surface hardness and wear resistance of quartz sand materials. The low friction coefficient of polytetrafluoroethylene powder makes the surface of quartz sand material smoother and can also improve the chemical corrosion resistance of quartz sand material. Antioxidant 168 can prevent polyurethane resin and other binders from oxidative aging during processing and use; with the synergy of the above binder components, quartz sand and binder are fully combined; good flexibility: not easy to break during wire drawing and printing; good flow performance: good extrusion effect and high quality of finished products.
[0015] In a preferred embodiment, the particle size of the quartz sand powder is -300 mesh. In the actual operation process, the quartz sand powder is passed through a 300 mesh sieve, and the sieve under is taken.
[0016] In a preferred solution, the mass ratio of the quartz sand powder to the binder is 3 to 4:1. The mass ratio of the quartz sand powder to the binder is controlled within the above range, and the performance of the obtained microfluidic chip is finally optimized. If too much binder is added, the overall hardness and rigidity of the material will be reduced, and the thermal stability of the material will be deteriorated; the flowability of the filament A will be deteriorated, and the difficulty of degreasing will be increased; if too little binder is added, the bonding strength between the quartz sand and the binder will be insufficient, and the filament A may not be able to be printed.
[0017] In a preferred embodiment, the quartz sand powder and the binder are mixed at a temperature of 120 to 150° C. for 20 to 30 minutes.
[0018] In a preferred embodiment, the diameter of the wire A is 1.70-1.80 mm.
[0019] In a preferred embodiment, the diameter of the wire B is 1.70-1.80 mm.
[0020] In a preferred embodiment, the parameters of the deposition printing are: the printing layer thickness is 0.1-0.3 mm, the platform temperature is 40-60° C., and the nozzle temperature is 180-220° C.
[0021] During the printing process, the parameters are controlled within the scope of the present invention, and the performance of the microfluidic chip finally obtained is optimal. If the temperature of the printing platform is too high, the material may be over-softened or deformed at the beginning of printing, resulting in deformation of the printed structure and excessive adhesion between the printed layer and the printing platform. If the temperature of the printing platform is too low, the low-temperature platform cannot provide enough heat to quickly cool the filament and fix it on the platform, and it will also affect the bonding force between the layers. If the nozzle temperature is too high: the rheological properties of the filament will change, becoming too thin, affecting the printing accuracy. If the nozzle temperature is too low, the fluidity of the filament will be greatly reduced, resulting in the filament being unable to be smoothly extruded from the nozzle.
[0022] In the actual operation process, a model of the microfluidic chip is established in the computer 3D modeling software, and the model file is stored in the STL format. The file is then cut directly using the slicing software to make the thickness of each layer machinable, and the final slicing file is imported into the FDM3D printer; then the two types of filaments are respectively placed in the feed port of the printer, the working parameters of the dual-filament FDM3D printer are set, the equipment is started, and printing is performed to obtain the working layer green body.
[0023] In a preferred embodiment, the degreasing method is solvent degreasing, the temperature of the solvent degreasing is 25° C. to 35° C., the time of the solvent degreasing is 8 to 12 hours, and the organic solvent used for the solvent degreasing is dichloromethane.
[0024] In the present invention, the binder and ABS in the microfluidic chip body are removed simultaneously by solvent degreasing.
[0025] In a preferred embodiment, the sintering process is as follows: heating the temperature to 400-600° C. at a heating rate of 5-10° C. / min, keeping the temperature for 20-30 min, and controlling the sintering pressure to 200-500 KPa.
[0026] In the present invention, sintering is performed at a relatively low temperature, and the microfluidic chip pays more attention to the characteristics such as the accuracy of the microstructure and the smoothness of the surface. Sintering at a relatively low temperature can better control the microstructure of the chip, avoid problems such as excessive shrinkage and deformation that may be caused by high-temperature sintering, and also help to maintain the integrity of the structure such as the internal channel of the chip. If the sintering temperature is too high, it will cause the main frame of the quartz sand to undergo a large thermal expansion. Due to the complex internal structure of the chip, the thermal expansion of different parts is uneven, which is prone to stress concentration, resulting in deformation or even cracking of the chip. In addition, it will cause excessive fusion of quartz sand particles, making the material too dense. For microfluidic chips, overly dense materials may affect their permeability, which is not conducive to the transmission of related substances when simulating the generation environment of hydrates in actual reservoirs.
[0027] The present invention also provides a 3D printed microfluidic chip prepared by the above preparation method.
[0028] The present invention also provides an application of a 3D-printed microfluidic chip prepared by the above preparation method, and the microfluidic chip is applied to the hydrate field.
[0029] Principles and advantages
[0030] The invention mixes quartz sand powder and a binder, performs granulation and wire drawing to obtain wire material A; then performs granulation and wire drawing on acrylonitrile-butadiene-styrene copolymer (ABS) to obtain wire material B; the two wire materials are respectively put into two feed ports of an FDM 3D printer, and according to a model of a microfluidic chip, the wire material A is used to print a microfluidic chip body, and the wire material B is used to fill a channel of the microfluidic chip to obtain a microfluidic chip green body; the microfluidic chip green body is degreased and sintered, and ABS is removed by post-processing to obtain a microfluidic chip.
[0031] Compared with the prior art, the advantages of the present invention are as follows:
[0032] (1) When printing microfluidic chips using fused deposition modeling (FDM) technology, the operating environment is safe, the equipment and material costs are low, the material utilization rate is high, it is suitable for complex structures, and it is easy to operate and maintain.
[0033] (2) The thermal conductivity of quartz sand is similar to that of natural reservoirs, which can better reflect the heat transfer during hydrate formation and better simulate the hydrate formation environment in actual reservoirs. At the same time, the hardness and stability of quartz sand enable it to withstand the pressure changes during hydrate formation. Its surface has a certain degree of hydrophilicity and can form good contact with water. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1This is a diagram of a quartz sand material 3D printed microfluidic chip model in Example 1, in which 1-air inlet, 2-chip base, 3-air outlet, and 4-microfluidic chip channel.
[0035] The accompanying drawings only show the simplest microchannel model. Of course, the microchannel can also have other complex structures, and multiple groups of microchannels each with an outlet and an inlet can be set on a chip. These structures can all be realized using the methods of the present invention. DETAILED DESCRIPTION
[0036] In order to make the content of the present invention more clearly understood, the present invention is further described in detail below according to specific implementation modes.
[0037] Example 1
[0038] A method for preparing a microfluidic chip based on 3D printing technology comprises the following steps:
[0039] Step 1): Preparation of solid powder: quartz sand powder is passed through a 300-mesh sieve, and the quartz sand under the sieve is mixed with a binder, and the mass ratio of powder to binder is 3:1; the mass fractions of the components of the binder are: polyurethane resin 60%, γ-aminopropyl triethoxysilane 15%, dibutyl phthalate 10%, nano titanium dioxide: 7%, polytetrafluoroethylene powder 7%, antioxidant 168 1%. The powder and the binder are weighed according to the above-mentioned design ratio.
[0040] Step 2): Mixing, granulation and drawing: After the powder and binder are evenly mixed together, they are placed in a mixer for mixing. The temperature during mixing is set to 150°C and the duration is 20 minutes. The purpose is to allow the powder and the binder to be tightly combined. After mixing, a plastic mixed internal mixing material will be obtained. This internal mixing material is taken out for granulation, and then the granules are put into the extruder for extrusion. Finally, a composite wire A with a diameter of 1.75±0.05mm that can be used for printing nozzles is obtained, and the traction and winding are completed on the traction machine. At the same time, acrylonitrile-butadiene-styrene copolymer (ABS) is granulated and drawn to obtain wire B with a diameter of 1.75±0.05mm.
[0041] Step 3): Printing model and parameter design: Create a microfluidic chip model in the modeling software and import it into the slicing software, set the printing layer thickness to 0.2mm, the filling degree to 100%, the nozzle temperature to 200℃, and the platform temperature to 50℃, perform slicing settings and export the final file, import the final file into the FDM printer, print according to the set parameters, and obtain the microfluidic chip green body after printing.
[0042] Step 4): Degreasing and removing ABS: The nozzle blank is first placed in a water bath heating pot for solvent degreasing. The degreasing solvent is dichloromethane. The temperature of the solvent degreasing is 25°C and the solvent degreasing time is 12 hours. At the same time, the ABS material in the microfluidic chip blank is removed and the channel of the microfluidic chip is restored. Shake the container once every hour to ensure the effect of degreasing and removing ABS.
[0043] Step 5): Sintering: After degreasing, the microfluidic chip green body is placed in a hot press sintering device, pressurized to 400 KPa, and the sintering furnace is heated from room temperature to 500 ° C at a heating rate of 5 ° C / min, kept warm for 30 minutes and then cooled to complete sintering to obtain a microfluidic chip.
[0044] The channel size error of the microfluidic chip prepared in this embodiment is within ±2%, the water flow control accuracy is within ±5%, the compressive strength is 20MPa, and the temperature range is -20°C-100°C, which can meet the experimental conditions of most hydrates, and the hydrate saturation generated reaches 70%-90%.
[0045] Example 2
[0046] A method for preparing a microfluidic chip based on 3D printing technology comprises the following steps:
[0047] Step 1): Preparation of solid powder: quartz sand powder is passed through a 300-mesh sieve, and the quartz sand under the sieve is mixed with a binder, and the mass ratio of powder to binder is 4:1; the mass fractions of the components of the binder are: polyurethane resin 50%, γ-aminopropyl triethoxysilane 15%, dibutyl phthalate 15%, nano titanium dioxide: 9%, polytetrafluoroethylene powder 9%, antioxidant 168 2%. The powder and the binder are weighed according to the above-mentioned design ratio.
[0048] Step 2): Mixing, granulation and drawing: After the powder and binder are evenly mixed together, they are placed in a mixer for mixing. The temperature is set to 130°C during mixing, and the duration is 30 minutes, in order to allow the powder and the binder to be tightly combined. After mixing, a plastic mixed internal compound is obtained. This internal compound is taken out for granulation, and then the granules are put into the extruder for extrusion. Finally, a composite wire A with a diameter of 1.75±0.05mm that can be used for printing nozzles is obtained, and the traction and winding are completed on the traction machine. At the same time, acrylonitrile-butadiene-styrene copolymer (ABS) is granulated and drawn to obtain wire B with a diameter of 1.75±0.05mm.
[0049] Step 3): Printing model and parameter design: Create a microfluidic chip model in the modeling software and import it into the slicing software, set the printing layer thickness to 0.2mm, the filling degree to 100%, the nozzle temperature to 200℃, and the platform temperature to 50℃, perform slicing settings and export the final file, import the final file into the FDM printer, print according to the set parameters, and obtain the microfluidic chip green body after printing.
[0050] Step 4): Degreasing and removing ABS: The nozzle blank is first placed in a water bath heating pot for solvent degreasing. The degreasing solvent is dichloromethane. The temperature of the solvent degreasing is 35°C and the solvent degreasing time is 8 hours. At the same time, the ABS material in the microfluidic chip blank is removed and the channel of the microfluidic chip is restored. Shake the container once every hour to ensure the effect of degreasing and removing ABS.
[0051] Step 5): Sintering: After degreasing, the microfluidic chip green body is placed in a hot press sintering device, pressurized to 300 KPa, and the sintering furnace is heated from room temperature to 600 ° C at a heating rate of 10 ° C / min, kept warm for 20 minutes and then cooled to complete sintering to obtain a microfluidic chip.
[0052] The channel size error of the microfluidic chip prepared in this embodiment is within ±2%, the water flow control accuracy is within ±5%, the compressive strength is 20MPa, and the temperature range is -20°C-100°C, which can meet the experimental conditions of most hydrates, and the hydrate saturation generated reaches 70%-90%.
[0053] Comparative Example 1
[0054] The other conditions were the same as those in Example 1, except that the polyurethane resin was not added to the binder, resulting in the microfluidic chip green body returning to a granular state after degreasing and sintering without forming.
[0055] Comparative Example 2
[0056] The other conditions were the same as those in Example 2, except that the degreasing time was less than 8 h, the green body was not completely degreased, the ABS in the channel was not completely removed, and the microfluidic chip obtained by sintering cracked and had limited functionality.
[0057] Comparative Example 3
[0058] Other conditions were the same as those in Example 1, except that polylactic acid was used as the filament B to fill the microfluidic chip channel. As a result, the channel wall partially collapsed during the molding process, affecting the shape accuracy of the channel.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a 3D printed microfluidic chip, characterized in that: The quartz sand powder and the binder are mixed, granulated and drawn to obtain the wire A; the acrylonitrile-butadiene-styrene copolymer is granulated and drawn to obtain the wire B; the wire A and the wire B are respectively placed in the two feed ports of the FDM3D printer, and are extruded and deposited through the nozzle for printing according to the model of the microfluidic chip, wherein the wire A prints the microfluidic chip body, and the wire B fills the channel of the microfluidic chip to obtain the microfluidic chip green body, and the microfluidic chip green body is degreased and sintered to obtain the microfluidic chip.
2. The method for preparing a 3D printed microfluidic chip according to claim 1, characterized in that: The binder is composed of the following by mass percentage: 50%-60% polyurethane resin, 10%-15% γ-aminopropyltriethoxysilane, 10%-15% dibutyl phthalate, 5%-10% nano titanium dioxide, 5%-10% polytetrafluoroethylene powder, and 1%-2% antioxidant 168.
3. A method for preparing a 3D printed microfluidic chip according to claim 1 or 2, characterized in that: The particle size of the quartz sand powder is -300 mesh.
4. A method for preparing a 3D printed microfluidic chip according to claim 1 or 2, characterized in that: The mass ratio of the quartz sand powder to the binder is 3 to 4:
1.
5. A method for preparing a 3D printed microfluidic chip according to claim 1 or 2, characterized in that: The temperature for mixing the quartz sand powder and the binder is 120-150°C and the time is 20-30 minutes; The diameter of the wire A is 1.70-1.80 mm; The diameter of the wire B is 1.70-1.80 mm.
6. A method for preparing a 3D printed microfluidic chip according to claim 1 or 2, characterized in that: The parameters of the deposition printing are: the printing layer thickness is 0.1-0.3 mm, the platform temperature is 40-60° C., and the nozzle temperature is 180-220° C.
7. A method for preparing a 3D printed microfluidic chip according to claim 1 or 2, characterized in that: The degreasing method is solvent degreasing, the temperature of the solvent degreasing is 25° C. to 35° C., the time of the solvent degreasing is 8 to 12 hours, and the organic solvent used for the solvent degreasing is dichloromethane.
8. A method for preparing a 3D printed microfluidic chip according to claim 1 or 2, characterized in that: The sintering process is: heating to 400-600° C. at a heating rate of 5-10° C. / min, keeping the temperature for 20-30 minutes, and controlling the sintering pressure to be 200-500 KPa.
9. A 3D printed microfluidic chip prepared by the preparation method according to any one of claims 1 to 8.
10. Application of a 3D printed microfluidic chip prepared by the preparation method according to any one of claims 1 to 8, characterized in that: The microfluidic chip is applied to the hydrate field.
Citation Information
Patent Citations
Preparation method for polymer micro-fluidic chip
CN103285950A
Universal chip for regenerating printing supplies
CN106418623A
3D printing molding method for colorful quartz glass with high light transmittance
CN109694181A
Micro-fluidic chip preparation method based on 3D printing device
CN115254215A
Three-dimensional printing
US20190091766A1